2008
DOI: 10.1111/j.1365-4632.2008.03690.x
|View full text |Cite
|
Sign up to set email alerts
|

Xanthelasma palpebrarum and its relation to atherosclerotic risk factors and lipoprotein (a)

Abstract: In patients with xanthelasma, no increase was observed in the rate or risk of cardiovascular disease. Moreover, no relationship was found between Lp (a) levels and xanthelasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 27 publications
8
32
1
1
Order By: Relevance
“…Increased LDL-C and reduced HDL-C have also been implicated in the causation of atherosclerosis and CVD 10. The presence of a family history in 27.5% in the present series is comparable with 29% and 22% reported by Gomez et al 25 and Ozdol et al ,26 respectively, and suggests that genetic factors may contribute to the pathogenesis of XP.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Increased LDL-C and reduced HDL-C have also been implicated in the causation of atherosclerosis and CVD 10. The presence of a family history in 27.5% in the present series is comparable with 29% and 22% reported by Gomez et al 25 and Ozdol et al ,26 respectively, and suggests that genetic factors may contribute to the pathogenesis of XP.…”
Section: Discussionsupporting
confidence: 87%
“…Contrary to this, Gomez et al 25 and Segal et al 32 concluded that XP did not increase the risk of CVD. Recently in a case–control study of 100 patients with XP, Ozdol et al 26 reported similar rates of clinically overt CVD and future cardiovascular risk as evaluated by the prevalence of cardiac risk factors and Framingham risk scores. The variable outcome may be attributed to the lack of appropriate selection of control groups and small study populations in some of the above studies.…”
Section: Discussionmentioning
confidence: 92%
“…Xanthelasma has been studied as a marker of premature atherosclerosis by discovering ultrasonographic thickening of the carotid intima [22]. Defects in lipoproteins, apolipoproteins (proteins that bind lipids and transport them through the lymphatic and circulatory systems), apoenzymes, and vascular permeability in the face of normal serum lipid levels are other possible contributing mechanisms for the genesis of xanthelasma [23-25]. In a recent study [26], immunohistochemical staining of paraffin sections of xanthelasmas revealed a wide range of upregulated inflammatory cofactors paralleling those found in the early stages of cardiac atherosclerotic plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…Though the exact cause is not known, disturbance in lipid metabolism may contribute to its pathogenesis. 2 XP appears as soft, velvety skin to yellow coloured macular, maculopapular and plaque like lesions over eyelids and around eyes. 3 Microscopically, XP is composed of foamy cells in the superficial dermis, where lipid-laden histiocytes can be seen.…”
Section: Introductionmentioning
confidence: 99%